(untitled) (Applied Biological Research, 2018)
Present study was carried out on the radius and ulna bones of five adult royal Bengal tiger skeleton to notice the characteristic features from other carnivores. The radius was slightly twisted bone with an antero-posteriorly flattened shaft and two extremities. The bicipital tuberosity was present on the proximal part posterior surface. On the distal aspect of posterior surface eight faint oblique lines were present. Proximal extremity had concave facet circumscribed by a bony rim which was sharp and prominent on its lateral part and blunt towards the medial side. Distal extremity was expanded and was about twice the size of proximal extremity. It had a large concave facet that extended medially and ventrally. Ulna was longer than the radius and was fattened medio-laterally. Proximal extremity had olecranon process, anconeus process and facet for humerus. Olecranon process possessed three tubercles. The caudal one was largest (trifid) and lateral tubercle was prominent and smooth and placed cranial to the medial one. Distal extremity was much smaller than the proximal extremity and had rounded facet towards the medial side which articulated with the distal extremity of radius. During morphometry of radius and ulna bones, a non-significant difference was noticed between the bones of two fore limbs which may be of biomechanical importance.